2021
DOI: 10.1249/mss.0000000000002661
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Exercise in Age Rats Improves Skeletal Muscle Function and MicroRNA Profile

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Inhibition of PTEN improved muscle function in Duchenne muscular dystrophy [ 33 ], and aerobic exercise had a negative effect on the expression of PTEN in mice [ 34 ]. Just recently, moderate training in rats was shown to block expression of PTEN, and it was discussed that thereby an age-related loss of muscle mass might be blocked on the level of the PI3K pathway [ 35 , 36 ]. Training also activated the p38 MAPK in the muscle of rats [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of PTEN improved muscle function in Duchenne muscular dystrophy [ 33 ], and aerobic exercise had a negative effect on the expression of PTEN in mice [ 34 ]. Just recently, moderate training in rats was shown to block expression of PTEN, and it was discussed that thereby an age-related loss of muscle mass might be blocked on the level of the PI3K pathway [ 35 , 36 ]. Training also activated the p38 MAPK in the muscle of rats [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Just recently, moderate training in rats was shown to block expression of PTEN, and it was discussed that thereby an age-related loss of muscle mass might be blocked on the level of the PI3K pathway [ 35 , 36 ]. Training also activated the p38 MAPK in the muscle of rats [ 36 ]. We identified activation of both PI3K and p38 MAPK in trained DUC mice but not in trained DUhTP mice, although we did not observe altered expression or activity of PTEN in response to exercise in our experimental system.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings of studies investigating these miRs after exercise are inconsistent. In one study, 14 days of exercise training caused no change in muscle miR29a in humans [63], nor did endurance exercise in rats alter miR 23a or 29a levels in skeletal muscle [64]. Conversely, another study found an increase in plasma miR29a in humans immediately after the completion of a marathon [65], and patients with Type 2 Diabetes Mellitus, who are at higher risk of kidney damage, had increased basal levels of miR29a in the muscle [66].…”
Section: Micro Rnamentioning
confidence: 99%
“…Thus, the AKT/PTEN pathway is critical for skeletal muscle hypertrophy and prevention of muscle atrophy 17 . Our previous studies have shown that lifelong exercise‐activated PTEN/AKT pathway and indirectly inhibited the HIPPO pathway activation 18 . Therefore, we investigated whether HIIT acts on HIPPO pathway to prevent muscle atrophy along with regulating AKT/PTEN pathway.…”
Section: Introductionmentioning
confidence: 99%
“…17 Our previous studies have shown that lifelong exercise-activated PTEN/AKT pathway and indirectly inhibited the HIPPO pathway activation. 18 Therefore, we investigated whether HIIT acts on HIPPO pathway to prevent muscle atrophy along with regulating AKT/PTEN pathway. Additionally, exerciseinduced constriction modified the expression of multiple miRNAs in human skeletal muscle, including miR-1, miR-133a, miR-133b, miR-378a, and miR-486.…”
Section: Introductionmentioning
confidence: 99%